تداولية الأفعال الكلامية في أحاديث الرسول صل الله عليه وسلم في رياض الصالحين للإمام النووي دراسة لنماذج مختارة - رانا بلحسن (My University, 2023)
Summary: Delebration is a linguistic field that complements structural linguistics it attempts to understand linguistic use through multiple contexts, speakers' purposes and the relationship of markers to its users. Therefore, speech acts are considered to be the cornerstone of deliberative linguistics. This study therefore seeks to reveal the circulation of verbal acts in the Holy Prophet in Riyad Al-Salhin book of imam nawawi in accordance with the division of Searl. The texts of the Holy Qur 'an and Hadith include news, compulsory, expressive, advertising and guidance, all of which are intended to carry out certain work that the prophet Mohammad wanted to inform and communicate -------------- ملخص: تعد التداولية ميدانا لغويا مكملا للسانيات البنيوية فهي تحاول فهم الاستعمال اللغوي من خلال سياقات متعددة ومقاصد المتكلمين وعلاقة العلامات بمستعمليها ومن ثمّ تعتبر أفعال الكلام ركيزة اللسانيات التداولية. لذلك تسعى هذه الدراسة للكشف عن تداولية الأفعال الكلامية في الحديث النبوي الشريف في كتاب رياض الصالحين للإمام النووي وذلك وفق تقسيم سورل. وقد ترواحت الأفعال الكلامية في كتاب رياض الصالحين والتي تضمنتها نصوص القرآن الكريم والحديث بين الإخبارية والإلزامية والتعبيرية والإعلانية والتوجيهية ،وجاءت كلها لتنجز عملا معينا أراد الرسول صلى الله عليه وسلم تبليغه وإيصاله. ------------------- Résumé : Pragmatique est un domaine linguistique qui complète linguistique structurel. Il tente de comprendre l’utilisation linguistique à travers de multiples contextes, les buts des locuteurs et la relation des marqueurs à ses utilisateurs. Par conséquent, les actes de parole sont considérés comme la pierre angulaire de la linguistique délibérative. Cette étude cherche donc à révéler la circulation des actes verbaux dans le Livre de l’Imam nawawi de Riyad Al-Salhin, conformément à la division de Searl. Les textes du Saint Coran et du Hadith comprennent des nouvelles, obligatoires, expressives, de la publicité et des conseils, qui sont tous destinés à effectuer certains travaux que Prophéte Mohamed informer et communiquer.